Adherence to Hemodialysis Therapy, Self-efficacy and Quality of Life of Chronic Kidney Disease Patients in the Hemodialysis Room - ., Asra; Susila, Arif; Rochman, Dadang; Gustin Rahayu, Trio; Lestari, Mira (KnE Social Sciences, 2023)
Hemodialysis is a renal replacement therapy that can prolong a patient’s life. The study aims to determine the relationship between adherence to hemodialysis therapy and self-efficacy with the quality of life of patients with chronic kidney disease in the hemodialysis room of the Cilegon City Hospital in 2019. This study used a quantitative design with a cross-sectional. The population of this study was composed of patients with chronic renal failure who underwent hemodialysis therapy. The number of samples were 47 respondents using the total sampling technique. The method used in this study was the Chi-square test. The results showed that 20 patients did not adhere to hemodialysis therapy (42.6%), self-efficacy (44.7%), poor quality of life was 21 patients (44.7%). A significant relationship was observed between adherence to hemodialysis therapy (P-value = 0.001), self-efficacy (P-value = 0.003), and quality of life. Future researchers are expected to continue this research with different research methods. Keywords: chronic kidney disease (CKD), hemodialysis, compliance, self-efficacy